2015
DOI: 10.1155/2015/419106
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Extract Improves Insulin Signaling and Attenuates Inflammation in Retroperitoneal Adipose Tissue Depot of Obese Rats

Abstract: Due to the high incidence and severity of obesity and its related disorders, it is highly desirable to develop new strategies to treat or even to prevent its development. We have previously described that Ginkgo biloba extract (GbE) improved insulin resistance and reduced body weight gain of obese rats. In the present study we aimed to evaluate the effect of GbE on both inflammatory cascade and insulin signaling in retroperitoneal fat depot of diet-induced obese rats. Rats were fed with high fat diet for 2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
6
48
0
Order By: Relevance
“…28 It is impressive that the previous studies have revealed the Ginkgo biloba extract could improve metabolic disorders in obese mice through targeting different receptors. 17,30 However, we found GB only enhanced hPXR transactivity, but not PPARa, PPARb, PPARg, LXRa, LXRb and FXR transactivities. Herein, we suspected GB may regular metabolic through PXR pathway.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…28 It is impressive that the previous studies have revealed the Ginkgo biloba extract could improve metabolic disorders in obese mice through targeting different receptors. 17,30 However, we found GB only enhanced hPXR transactivity, but not PPARa, PPARb, PPARg, LXRa, LXRb and FXR transactivities. Herein, we suspected GB may regular metabolic through PXR pathway.…”
Section: Discussionmentioning
confidence: 51%
“…40 However, our study shown that GB displayed no change of the expression of MCP-1, IL-1b and TNF-a in the liver of DIO mice, although Ginkgo biloba extract attenuates inammation in retroperitoneal adipose tissue depot of obese rats. 30 This difference may be caused by the animal model. In our study, the liver of DIO mice did not show signicant inammation response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, more studies are needed to establish if oxidative stress is the cause or the consequence of therapeutic properties of G. biloba extracts. For instance, G. biloba extracts have antiinflammatory properties in different in vitro and in vivo models (Apetz et al, 2014;Siegel et al, 2014;Tisato et al, 2013;Chen et al, 2014;Hirata et al, 2015) and the inhibition of inflammatory response can decrease the oxidative stress. In short, the complex interplay between primary cellular responses and oxidative stress in chronic degenerative diseases and the modulation of this interaction by plant extracts need more detailed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ginkgolides, extracted from the Ginkgo biloba leaf, are a group of ingredients with a wide range of pharmacological activity, including neuroprotective (Ahlemeyer & Krieglstein, ; Calapai et al, ; Kim, Lee, Lee, & Kim, ; Saleem, Zhuang, Biswal, Christen, & Dore, ) and anti‐inflammatory effects (Hirata et al, ; Ilieva et al, ; Lippi, Targher, & Guidi, ). They are also natural antagonists of the platelet‐activating factor receptor (Kurihara, Wardlaw, Moqbel, & Kay, ; Lamant, Mauco, Braquet, Chap, & Douste‐Blazy, ), and show promising effects on neuronal damage and cardiac diseases (Haines et al, ; Smith, Maclennan, & Darlington, ).…”
Section: Introductionmentioning
confidence: 99%